The effectiveness of cash and cash plus interventions on livelihoods outcomes: Evidence from a systematic review and meta-analysis - Leight, Jessica; Hirvonen, Kalle; Zafar, Sarim (International Food Policy Research Institute, 2024)
Cash transfer programs have become increasingly popular tools for fighting chronic poverty and food insecurity in lowand middle-income countries (Fiszbein and Schady, 2009; USAID, 2022; WFP, 2023). Cash transfers offer recipients flexibility by permitting them to finance immediate consumption needs or to increase future income streams through investments and savings. Moreover, these programs are generally feasible to implement and scale across diverse contexts. While studies consistently show cash transfers effectively reduce poverty in the short term, the evidence on their long-term impact is less clear.